The Development of Human Resource Management Pattern Enhancing Human Resource Strategic Partnership of Non-profit Organization - Parinya Roonpho ปริญญา หรุ่นโพธิ์; Teerawat Chantuk ธีระวัฒน์ จันทึก; ศิริวงศ์ พิทักษ์ (Dusit Thani College Journal, 2018)
The purposes of this research paper are 1) to develop the elements of strategy for human resource management system, 2) to develop the human resource management pattern enhancing human resource strategic partnership of non-profit organization. The Pajek technique was adopt and used in order to analyze the information network. There were 17 human resource management experts to contribute the information for First and Second round-Ethnographic Delphi Futures Research (EDFR). And also Participatory Action Research (PAR) was conducted. The Cohen’s Kappa Coefficient was applied for evaluating consistency. The result reveals that the elements of the development of human resource management pattern enhancing Human Resource Strategic Partnership of Non-Profit Organization are the role of Strategic partner, the role of Administrative Experts, the roles of Change Agent, and the roles of Employee Champion, that the combination of four roles leads to the efficient strategic partner of the organization.